Genome‐Wide Association Study of Acute Renal Graft Rejection. Issue 1 (22nd July 2016) - Ghisdal, L.; Baron, C.; Lebranchu, Y.; Viklický, O.; Konarikova, A.; Naesens, M.; Kuypers, D.; Dinic, M.; Alamartine, E.; Touchard, G.; Antoine, T.; Essig, M.; et al.
Abstract : Acute renal rejection is a major risk factor for chronic allograft dysfunction and long‐term graft loss. We performed a genome‐wide association study to detect loci associated with biopsy‐proven acute T cell–mediated rejection occurring in the first year after renal transplantation. In a discovery cohort of 4127 European renal allograft recipients transplanted in eight European centers, we used a DNA pooling approach to compare 275 cases and 503 controls. In an independent replication cohort of 2765 patients transplanted in two European countries, we identified 313 cases and 531 controls, in whom we genotyped individually the most significant single nucleotide polymorphisms (SNPs) from the discovery cohort. In the discovery cohort, we found five candidate loci tagged by a number of contiguous SNPs (more than five) that was never reached in iterative in silico permutations of our experimental data. In the replication cohort, two loci remained significantly associated with acute rejection in both univariate and multivariate analysis. One locus encompasses PTPRO, coding for a receptor‐type tyrosine kinase essential for B cell receptor signaling. The other locus involves ciliary gene CCDC67, in line with the emerging concept of a shared building design between the immune synapse and the primary cilium. Abstract : A genome‐wide association study strongly implicates B cell tyrosine kinase PTPRO and ciliary gene CCDC67 in acute renal allograft rejection.